Experience of women with perinatal mood and anxiety disorder and the supportive role of obstetric and gynecologic nurses - R., Hemavathi; Bhakare, Samruddhi Suresh; Kamal D., Abisha; Chetanmala Devi, Khumbongmayum; Umar, Mohammed; Badduri, Phanindrareddy; Bakshi, Pooja; Balamurugan (International Journal of Contemporary Pediatrics, 2026)
Perinatal mood and anxiety disorders (PMADs) represent a significant public health concern affecting women during pregnancy and up to one year postpartum, with substantial consequences for maternal well-being, obstetric outcomes, and infant development. Despite their high prevalence, PMADs remain under-recognized and under-treated, largely due to stigma, limited awareness, and fragmented healthcare services. This comprehensive review synthesizes current evidence on women’s lived experiences of PMADs and examines the supportive role of obstetric and gynecologic nurses in identification, intervention, and continuity of care. A systematic search of major biomedical, nursing, and psychological databases was conducted, incorporating quantitative, qualitative, and mixed-methods studies, systematic reviews, and clinical practice guidelines. Findings indicate that women commonly experience emotional distress, anxiety, guilt, and fear of judgment, which contribute to delayed help-seeking and reduced engagement with mental health services. Obstetric and gynecologic nurses emerged as key facilitators of perinatal mental health care due to their sustained contact with women across the perinatal continuum. Evidence supports the effectiveness of nurse-led screening, psychoeducation, emotional support, and brief psychological interventions in reducing depressive and anxiety symptoms, particularly for mild to moderate PMADs. However, gaps in training, time constraints, and inadequate referral pathways limit optimal nursing involvement. Strengthening nurse education, integrating mental health services within obstetric care, and implementing structured care pathways are essential to improving outcomes. Enhancing the role of obstetric and gynecologic nurses offers a feasible and effective strategy to address the burden of PMADs and improve maternal and infant health outcomes.